2007
DOI: 10.1021/la062229j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Reduced Mobility Layer on the Structural Relaxation Dynamics of Aluminum Capped Ultrathin Films of Poly(ethylene terephthalate)

Abstract: The structural dynamics of ultrathin polymer films of poly(ethylene terephthalate) capped between aluminum electrodes have been investigated by dielectric relaxation spectroscopy. A deviation from bulk behavior, appearing as an increase of the relaxation time at a fixed temperature, is observed for films of thickness below 35 nm. The slowing down acts as a constant shift factor independent from the temperature, and the fragility is constant. The interfacial energy between aluminum and poly(ethylene terephthala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 50 publications
12
115
0
Order By: Relevance
“…It is well-known from studies in the context of polymer thin films that interfaces perturb the glass transition temperature, T g , [197][198][199][200][201] and several simulation studies have shown that the segmental dynamics near NP surfaces are also distinct from the bulk. [202][203][204] The general trend that has emerged is that the polymer dynamics typically slows down if the NP-polymer interaction is attractive (T g increases) and speeds up if this interaction is strongly repulsive (T g decreases).…”
Section: Dynamics In Polymer Nanocompositesmentioning
confidence: 99%
“…It is well-known from studies in the context of polymer thin films that interfaces perturb the glass transition temperature, T g , [197][198][199][200][201] and several simulation studies have shown that the segmental dynamics near NP surfaces are also distinct from the bulk. [202][203][204] The general trend that has emerged is that the polymer dynamics typically slows down if the NP-polymer interaction is attractive (T g increases) and speeds up if this interaction is strongly repulsive (T g decreases).…”
Section: Dynamics In Polymer Nanocompositesmentioning
confidence: 99%
“…Such proportionality justifies the use of De as a parameter to monitor adsorption; in fact, as in the case of cold crystallization, [8,9] partial or total immobilization of the chains limits the solid angle over which dipoles can reorient, yielding a reduction in the dielectric strength. [10] In fact,…”
Section: Introductionmentioning
confidence: 99%
“…The interfacial energy γ PS/Al between aluminium and PS was calculated on the basis of the Good-Girifalco-Fowkes combining rule 46 , which takes into account both polar and dispersive contributions: ] from contact angle measurements on layers thermally evaporated under similar conditions performed in a previous work by one of the authors 48 . The contribution of the surface oxide layer to influencing the wettability of the metal is reflected in the values of the contact angle and is thus taken into account in the parameters of equation (2).…”
mentioning
confidence: 99%